Memory SARS-CoV-2 T-cell response in convalescent COVID-19 patients with undetectable specific IgG antibodies: a comparative study - Fernández-Moreno, Raquel; Valle-Arroyo, Jorge; Páez-Vega, Aurora; Salinas, Ana; Cano, Angela; Pérez, Ana B.; Torre-Cisneros, Julián; Cantisán, Sara (Frontiers in Immunology, 2023)
During the COVID-19 pandemic, a variable percentage of patients with SARS-CoV-2 infection failed to elicit humoral response. This study investigates whether patients with undetectable SARS-CoV-2 IgG are able to generate SARS-CoV-2 memory T cells with proliferative capacity upon stimulation. A total of 119 participants (86 PCR-confirmed COVID-19 patients and 33 healthy controls) were randomly filtered from an initial cohort. COVID-19 patients were enrolled ≥ 3 months after the last PCR positive. Of these 86 patients, 59 had detectable (seropositive) and 27 had undetectable (seronegative) SARS-CoV-2 IgG. Seropositive patients were subclassified as asymptomatic/mild or severe according to the oxygen supplementation requirement. Proliferative T-cell response after whole blood stimulation was assessed using the FASCIA assay. SARS-CoV-2 CD3+ and CD4+ T cells showed significantly lower proliferative response in seronegative than in seropositive patients. The ROC curve analysis indicated that ≥ 5 CD4+ blasts/µL of blood defined a “positive SARS-CoV-2 T-cell response”. According to this cut-off, 93.2% of seropositive patients had a positive T-cell response compared to 50% of seronegative patients and 20% of negative controls (chi-square; p < 0.001). This proliferative assay is useful not only to discriminate convalescent patients from negative controls, but also to distinguish seropositive patients from those with undetectable SARS-CoV-2 IgG antibodies. Memory T cells in seronegative patients are able to respond to SARS-CoV-2 peptides, although at a lower magnitude than seropositive patients.